(3GdCOhjI GdeaQOIs - (3CHh LYaQ CMeO Hf eMeO Hf eMeO GdeYQha HGHf CHi GdCTYK,J (B365 (3g` s
(3ChdgG (B:s
(3HGH GdPGd PgH bGd Mfjf (B: (3GdPgH ai ZGjI GdEYJOGd jfaY ef hLY GdbdH GdeRef s
(3BNQgG (B:s
[ (3ef (B] (3jYQV dg GdUQY hcGf ef eYOJg TaGA dGeMGdg fLRJ GdebGdI GdKGdKI ef cJGH bhi GdGOhjI GdeaQOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B201s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(291(3b(B) s
Keywords: (3GdWHs